"They say it's more aggressive in black women": Biosociality, breast cancer, and becoming a population "at risk". Issue 3 (15th February 2019) - Brown, Tim; Dyck, Isabel; Greenhough, Beth; Raven‐Ellison, Menah; Ornstein, Mark; Duffy, Stephen W.
Abstract : Recent geographical scholarship has drawn attention to the ways in which the practice of public health constructs particular bodies and populations as "risky." From a biopolitical perspective, this status of being "at risk" offers the basis for an emergent biosociality, groups brought together by a shared vulnerability to disease, which then forms the basis for both state‐led public health interventions and community‐driven advocacy and support. Critics, however, suggest a focus on biosociality can act to obscure other dimensions of individual and community identity, dimensions that can play a key role in determining both health status and the success of healthcare interventions. This paper draws together insights from geography, anthropology, and sociology with empirical evidence from focus groups collected as part of an evaluation of a breast cancer awareness DVD distributed in the London borough of Hackney. We explore the extent to which the DVD, by defining a specific group (black women aged 25–50) as being at increased risk of developing more severe forms of breast cancer at a younger age, led to the formation of a biosocial community. Themes emerging from the analysis of focus group transcripts present a complex picture. At times our participants clearly aligned themselves with this biosocial collective, drawing on a shared Black political identity, assumptions of a common African genetic heritage, experiences of diaspora, and perceived similarities in lifestyles and bodily norms. At other times, however, this shared sense of belonging fragmented in light of perceived differences in culture, lifestyle, and community which nuanced both participants' sense of being "at risk" and how they might (or might not) seek to manage that risk. Our findings suggest that biosociality is a fragile and heterogeneous accomplishment, with implications for the way we practise medical and social science research, design community‐targeted public health interventions and conceptualise risk. Abstract : This paper draws together insights from geography, anthropology and sociology with empirical evidence from focus groups collected as part of an evaluation of a breast cancer awareness DVD distributed in the London borough of Hackney. We explore the extent to which the DVD, by defining a specific group (black women aged 25–50) as being at increased risk of developing more severe forms of breast cancer at a younger age, led to the formation of a biosocial community. Themes emerging from the analysis of focus group transcripts show how at times our participants clearly aligned themselves with this biosocial collective, but at other times this shared sense of belonging fragmented in light of perceived differences in culture, lifestyle, and community which nuanced both participants' sense of being "at risk" and how they might (or might not) seek to manage that risk. Our findings suggest that biosociality is a fragile and heterogeneous accomplishment, with implications for the way we practise medical and social science research, design community‐targeted public health interventions, and conceptualise risk.